(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
The biggest global cause of morbidity and mortality, according to the World Health Organization, are cardiovascular diseases (CVDs). Consequently, there is a need for new therapeutic modalities that will complement current CVD care tools. To evaluate the effectiveness of the Ischemia Reversal Program along with a restricted diet in an elderly myocardial ischemic patient with other comorbidities like Hypertension (HTN) and Hypokinesia. 60-year-old male had a myocardial ischemia episode in April 2020 and received standard allopathic medical care. The patient had a history of HTN. This patient opted for Ischemia Reversal Program (IRP) and dietary modification with Ayurveda-based medicines as an add-on complementary treatment to accelerate the healing process. The patient had elevated HTN (SBP/DBP: 123/74) according to the ambulatory blood pressure monitoring (ABMP) report which was reduced post-intervention (SBP/DBP: 109/66). The patient also showed hypokinetic anterior wall LV according to the 2D ECHO report while the post-intervention 2D ECHO report showed no regional wall motion abnormality. Findings of our study suggest that IRP which includes Ayurveda-based Panchakarma therapy along with dietary modifications can serve as treatment for patients with myocardial ischemia and other comorbidities like HTN, and hypokinesia.